Hommage à Georges Eekhoud. Né à Anvers en 1854, mort à Bruxelles le 24 mai 1927. [Sous la red. de] H. Day [avec collab. de C. Lemonnier, E. Verhaeren, M. Elskamp] e.a ("Pensée et Action", 1947)
Avec bibliogr., ills. et prt.